INFLUENCE OF KNOWLEDGE OF MANAGEMENT, PRINCIPALS’ ATTITUDE, AND EFFECTIVENESS OF PRODIRA TOWARDS SCHOOL PERFORMANCE IN GORONTALO PROVINCIAL - ARSYAD, ARFAN (PPs UNJ, 2016)
The objective of this research is to study the direct effect of the principals’ knowledge of management, the principals’ attitudes, and the effectiveness of Prodira towards school perfomance. This research used the survey method. The technique of collecting data using questionnaires and tests. The data analysis was done using descriptive analysis and inferential analysis with the approach of path analysis. The results are: (1) the principals’ knowledge of management has a directly positive effect towards the school performance; (2) the principals’ attitudes has a directly positive effect towards the school performance; (3) the effectiveness of Prodira has a directly positive effect towards the school performance; (4) the principals’ knowledge of management has a directly positive effect towards the effectiveness of Prodira; (5) the principals’ attitudes has a directly positive effect towards the effectiveness of Prodira. Also found among the three predictor variables, the effectiveness of Prodira highest effect towards the school performance.